Religious pluralism in the region (2020)
The religious outlook in the region is a reflection of the change of process that´s generated in all humanity. Globalization permeates the human being with new ways of seeing the world and relates them with the divine, the gods, the sacred or holy. Religious diversity is as primitive as religion itself, for its identical cultural and historical connotations. In the so-called Christian era, there have been many religious confrontations; from the persecution of Christianity rising twenty centuries ago until the division of the Church, through socio-political rivalry with various religions in the world, up to contemporary times with syncretism and globalizing nuances that suggest a religious convergence in different human contexts. Against this plural scenery, the ecclesial ministry should take the call to evangelize, generating a religious dialogue and ecumenism, to offer Christianity from the inclusion and appreciation of different religious and spiritual manifestations, without spoiling its redemptive message.